205k views
1 vote
Which facts could be applied to simplify this expression check all that apply 5x+3y+(-x)+6z

User Sudocracy
by
5.8k points

2 Answers

6 votes
I think polynomial would work
User RaymondChou
by
5.8k points
4 votes

Answer:

The simplified form of the given expression
\Rightarrow (5-1)x+3y+6z is
4x+3y+6z

Explanation:

Consider the given expression,
5x+3y+(-x)+6z

We have to simplify the expression,

We can apply


ax-bx=(a-b)x , also,


+(-bx)=-bx

Thus, applying the above facts, the given expression becomes,


\Rightarrow 5x+3y-x+6z


\Rightarrow (5-1)x+3y+6z


\Rightarrow 4x+3y+6z

Thus, the simplified form of the given expression
\Rightarrow (5-1)x+3y+6z is
4x+3y+6z using the two facts stated above.


User Thugsb
by
6.7k points